Correlations of inflammatory processes caused by cerebral stroke with the outcome of the disease - A. Vaitkus; J. Valinčiūtė; S. Gylytė (Neurologijos seminarai)
Introduction. Inflammation plays a central role in the pathogenesis of stroke, so understanding inflammatory processes can greatly improve stroke treatment options. In this analysis, we review the positive and negative role of neuroinflammatory mechanisms in stroke. Negative influence of inflammatory cells and mediators in brain injury patients. All neuroinflammatory reactions and mediators play a negative role in initiating the pathological response to stroke and thus promote the development of inflammatory processes. Nosocomial infection. Elevated inflammatory markers and other prognostic factors are directly associated with higher rates of in-hospital complications such as pneumonia, urinary tract infection, and unfavorable stroke outcomes. New treatment directions can significantly improve clinical outcomes by reducing the incidence of hospital-acquired infections, which are one of the main complications after stroke. Vascular dementia. Stroke is a causative factor in vascular dementia, but certain neuroinflammatory processes in the brain are also involved. These processes may have detrimental effects on cognitive function after stroke. Therapeutic approaches that enhance pro-inflammatory cytokines and the immune system may be useful in preventing cognitive dysfunction, particularly after stroke. Physical disability. A stroke associated with ischemic, hemorrhagic, and neuroinflammatory processes in the course of the disease can cause a reduction or increase in physical disability and neurological deficit, which are very important for daily activities and quality of life. Positive influence of inflammatory cells and mediators in brain injury patients. All inflammatory cells and mediators play a positive role in complicating the pathological response to stroke and also in maintaining brain cell homeostasis. Discussion. Since the situation in this matter is quite controversial, a debatable question arises whether inflammatory processes have a positive or negative effect on the course and outcome of the disease in patients with stroke. Conclusions. After reviewing the latest scientific articles on this topic, we can say that the inflammatory process plays an ambiguous role in the pathogenesis of stroke and that its influence on the course and outcome of the disease can be both positive and negative. Therefore, today it is necessary to carry out more detailed scientific research in order to gain a deeper understanding of this issue and to achieve a better cure for the disease.